Post-mortem fungal colonization pattern during 6 weeks: Two case studies. (August 2018) - Di Piazza, Simone; Zotti, Mirca; Barranco, Rosario; Cecchi, Grazia; Greco, Giuseppe; Ventura, Francesco
Highlights: Data about 6 weeks mycological monitoring on two real corpses are reported. Fungi give information about perimortem and post-mortem environmental conditions. Microfungal maturation provides information to determine the post-mortem interval. Fungi can give information about the movement of the corpse. Abstract: The present study reports the mycological data collected from two corpses preserved in controlled conditions and monitored for 6 weeks at the mortuary. On the whole during the monitoring more than 70 fungal CFU (Colony Forming Units) were sampled from the corpses. The data collected were used to map the body fungal colonization of the corpses during 6 weeks. The two body maps show a huge difference between these cases, mainly due to the perimortem conditions. In particular, in the case one the facial area colonised by fungi rose from 15% to 63% in six weeks, while the fungal colonization of case two was about 1% for the whole monitoring period. This work shows, for the first time, the data about the pattern of colonization and distribution of fungi on real corpses after death and argues about the influence of perimortem settings on fungal colonization. Moreover, the paper suggests exploiting the study of fungal colony development and maturation to assess post-mortem interval (PMI).